2020
DOI: 10.1073/pnas.1921231117
|View full text |Cite
|
Sign up to set email alerts
|

Aerosols enhance cloud lifetime and brightness along the stratus-to-cumulus transition

Abstract: Anthropogenic aerosols are hypothesized to enhance planetary albedo and offset some of the warming due to the buildup of greenhouse gases in Earth’s atmosphere. Aerosols can enhance the coverage, reflectance, and lifetime of warm low-level clouds. However, the relationship between cloud lifetime and aerosol concentration has been challenging to measure from polar orbiting satellites. We estimate two timescales relating to the formation and persistence of low-level clouds over 1○×1○ spatial domains using multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
95
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(132 citation statements)
references
References 52 publications
9
95
1
Order By: Relevance
“…Such trajectory approaches are particularly useful when they exploit the high temporal resolution that is available from geostationary satellites. Aerosol retrievals from geostationary satellites may be combined using trajectory modelling to link these to clouds that form in these air masses (Kikuchi et al, 2018), or also the aerosol retrieval from a polar orbiter could be related to clouds retrieved from geostationary satellites that form in the same air masses (Christensen et al, 2020).…”
Section: Horizontal Co-locationmentioning
confidence: 99%
See 1 more Smart Citation
“…Such trajectory approaches are particularly useful when they exploit the high temporal resolution that is available from geostationary satellites. Aerosol retrievals from geostationary satellites may be combined using trajectory modelling to link these to clouds that form in these air masses (Kikuchi et al, 2018), or also the aerosol retrieval from a polar orbiter could be related to clouds retrieved from geostationary satellites that form in the same air masses (Christensen et al, 2020).…”
Section: Horizontal Co-locationmentioning
confidence: 99%
“…Aerosols can induce transitions between cloud regimes, for instance by changing drizzle behaviour (Rosenfeld et al, 2006;Feingold et al, 2010;Wood et al, 2011). The direction and magnitude of these changes depends on the cloud state and regime, because responses to aerosol changes occur due to processes spanning a range from microphysics to the mesoscale (Christensen and Stephens, 2012;Kazil et al, 2011;Wang et al, 2011). These processes include precipitation suppression (Albrecht, 1989), rapid feedbacks involving cloud-top entrainment (Ackerman et al, 2004;Bretherton et al, 2007;Hill et al, 2009;Bulatovic et al, 2019) and rapid feedbacks involving cloud lateral entrainment (Xue and Feingold, 2006;Small et al, 2009) as well as responses in dynamics (Xue et al, 2008;Stevens and Feingold, 2009;Wang and Feingold, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the aerosol perturbations can impart evaporation-entrainment feedback (particularly for non-precipitating cumulus clouds) to shorten the cloud lifespan [52]. However, it was also reported that anthropogenic aerosols can suppress the precipitation to yield clouds with longer lifespans, higher liquid water content, and larger fractional cloudiness [52,53]. Hence, further studies are needed to clarify the contrasting observations to pinpoint the exact influence of anthropogenic aerosols on cloud lifespan in the Arctic region.…”
Section: Air Pollution and Emissionsmentioning
confidence: 99%
“…Meskhidze et al (2009) and Gryspeerdt et al (2014) showed that short term development is also correlated to the aerosol environment, but that accounting for the initial cloud state is vital. This technique has recently been extended to longer timescales (Christensen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%